Analisis Perbandingan Akad Salam Dan Istishna’ Sebagai Instrumen Pembiayaan Syariah - Rio Panji Saputra; Zubaidah Assyifa; Nilam Erman; Merry Meilany; Diany Mairiza (Multidisciplinary Journal of Religion and Social Sciences, 2026)
Salam and istishna contracts are two transaction instruments in Islamic jurisprudence (fiqh muamalah) that hold significant potential as alternative financing instruments in Islamic banking, yet their application in Indonesia remains far from optimal. This article aims to comparatively analyze the fundamental concepts, operational mechanisms, and implementation of salam and istishna contracts within Indonesia's Islamic financing system. This study employs a qualitative approach using library research method through descriptive-comparative analysis of various relevant scientific literature sources. The findings reveal that although both contracts share similarities in that the object of transaction does not yet exist at the time of agreement, they differ substantially in terms of payment mechanisms, cancellation provisions, and the scope of financed objects. The salam contract is more relevant for agricultural sector financing, while the istishna contract is more predominantly applied in the construction and manufacturing sectors. The low implementation of both contracts is attributed to their high risk profiles, limited human resource capacity, and the availability of simpler alternative products. Synergistic efforts among regulators, Islamic banking institutions, and the government are required to optimize both contracts as inclusive and sustainable Islamic financing instruments.